Crohn's disease and pregnancy. Issue 1 (January 1984) - Khosla, R; Willoughby, C P; Jewell, D P
Abstract : Infertility and the outcome of pregnancy has been examined in 112 married women with Crohn's disease who were below the age of 45 years. Fifty four patients were available for study. The infertility rate (12%) was similar to that seen in the general population. Patients who had active disease at the time of conception continued to have symptoms and they mostly failed to go into satisfactory remission despite therapy. Furthermore, there was a high rate (35%) of spontaneous abortion in this group. In contrast, patients whose disease was in remission at the time of conception had a normal pregnancy and, in the majority, the Crohn's disease remained quiescent.